Alignment in Online Text-Based Chats: Cross-Cultural Case Study Research - Bekar Mira (Blazhe Koneski Faculty of Philology, Skopje, Ss. Cyril and Methodius University, 2017)
Our communication is driven by accommodation of our social identities as members of various communities of practice. During interacation, humans engage in constant multi-dimensional processes of accommodation or alignment. This exploratory cross-linguistic study describes the online text-based chatting practices of three participants ho chat in Macedonian (L1) and English (L2).
Keywords: alignment, text-based online chat, conversation analysis, discourse analysis